Перевал: роман / А. А. Тамоников - Тамоников Александр Александрович (Спецназ, 2012)
Экземпляры: Ф. 12 (20231204) / Инвентарный номер: 50189 / Цена: 30.00 / Сис.шифр: 84(2Рос-Рус)6-4 / Авт.знак: Т 17 / ББК: 84(2Рос-Рус)6-4